Proposed New Strong Ground Motion Attenuation Relations for Subduction Zone Earthquakes - Dedi Apriadi (Institut Teknologi Bandung, 2004)
Abstrak. Tulisan ini menyajikan usulan fungsi atenuasi terbaru untuk percepatan maksimum gempa di permukaan tanah tipe gempa subduksi interface dan intraslab pada moment magnitude lebih besar sama dengan 5 dan jarak 10 km sampai 500 km di batuan. Fungsi atenuasi telah dikembangkan dengan pendekatan Jaringan Syaraf Tiruan (JST) menggunakan algoritma propagasi balik. Studi memperlihatkan bahwa fungsi atenuasi berdasarkan JST akurat dan andal untuk memprediksi percepatan maksimum gempa. Studi parameter berbagai faktor input dari fungsi atenuasi juga telah dilakukan dan hasilnya akan disajikan di dalam tulisan ini.Abstract. This paper present proposed new attenuation relations at rock sites for peak ground acceleration for subduction zone interface and intraslab earthquakes of moment magnitude M 5 and greater and for distance of 10 to 500 km. The relations were developed by Artificial Neural Networks (ANN) approach using a back propagation algorithm. Studies show that the ANN-based attenuation relation is reliable and accurate to predict peak ground acceleration (PGA) due to earthquakes. Parameters studies of the various input factors of attenuation relations were also performed in this study and its results will be presented in this paper.